To multiply numbers with exponents, the base numbers must be the same; then we simply add the exponents. For example:
x4 = x x x x and x3 = x x x
Because multiplication is both associative and commutative, we can solve these equations as one:
x4 x3 = x x x x x x x = x7
So the end result, x7, is equivalent to x4 + 3:
x4 x3 = (x x x x) (x x x) = x4 + 3 = x7
This presumes that both the bases are the same. In other words, for example, we couldn't multiply 22 by 33 because the bases are not the same.